Emotional states of Angolan patients with dentomaxillofacial anomalies - Yosvany Herrero Solano; Pedro Luis Sánchez Sagué (Universidad de Ciencias Médicas de Granma, 2022)
Introduction: Dentomaxillofacial anomalies include alterations in growth, development and physiology of the anatomical components that make up the stomatognathic system, their prevention could be the solution to reduce the presence of this entity that causes so many functional, aesthetic and psychological discomforts in children, adolescents and young people. Objective: to identify the emotional states of Angolan patients with dentomaxillofacial anomalies. Methods: an observational, descriptive, cross-sectional study was carried out in 35 patients with dentomaxillofacial anomalies, treated at the orthodontic clinic of the Meditex-Alvalade Dental Clinic, in Luanda, Angola, between August 2021 and February 2022. Tests were applied to evaluate the emotional experience and self-esteem, as psychological states that may be affected in patients with dentomaxillofacial anomalies. Descriptive statistics measures were used for the summary of the information, which were number and percent. Results: the patients presented more than one emotion, the most significant were sadness with moderate (51,42 %) and intense levels (31,42 %), anguish with intense levels (40,00 %), rejection (25,71 %) at a moderate level and restlessness (25,71 %) and distrust (25,71 %) with a low level of experiential intensity; 45,71 % of the patients showed a medium level of self-esteem, followed by 34,28 % with a low level. Conclusions: Angolan patients with dentomaxillofacial anomalies experience emotions such as sadness, anguish, rejection, restlessness and distrust and medium and low levels of self-esteem.